KESEHATAN MENTAL SISWA YANG ORANGTUANYA BERCERAI DI SMP NEGERI 25 PEKANBARU - Ceria Galossa Victoria; Tri Umari; Rosmawati Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Mental hygiene is avoid someone from symptoms of mental disorder. Parental divorce can provide impact for child both of positive and negative. Based of phenomenon that occure at SMP Negeri 25 Pekanbaru consist of students often doing truant of school, students feel embarrassed and inferior to make a friend with someone, students rarely come to school, students are too easy emotions. The purpose of this research are to find out students mental hygiene of parental divorce, to find out students mental hygiene consist as psychology aspect and social aspect. The research use 30 students as subject of parental divorce. The research used descriptive method with quantitatif approach. The instrument of research use a questionnaire with likert scale. Technique collection data is used total sampling. The result of the research is students mental hygiene of parental divorce is in high category. It mean their mental hygiene of parental divorce is good condition. Category mental hygiene of the man gender is higer than woman gender students. Based of psychic aspect students generally has respect caracter and care about her/his self and other self. Based of social aspect students being tolerant and wannt to accept, regardless of social class, level of education, political, religion, tribe, race or skin color. For that students are expected can to increase mental hygiene to be better, to parents are expected can to optimalized role and to the teachers at school are expected to more pay attention for students development.Keyword : Students Mental Hygiene, Parental Divorce